Influence of Olfactory and Visual Sensory Stimuli in the Perfume-Purchase Decision - Cuesta, Fabián; Paida, Gabriela; Buele, Irene (International Review of Management and Marketing, 2020)
Neuromarketing has evolved in marketing practices, especially in the study of consumer behavior; however, in Ecuador this technique is still unknown, because they are limited to traditional marketing. The current research aims to determine the influence of olfactory and visual sensory stimuli in the decision making to purchase perfumes, using an experimental and conclusive investigation. 5,980 students at Politécnica Salesiana University in Cuenca participated in this study. Through the application of 361 surveys, fragrance preferences were determined by gender, obtaining that, women prefer floral fragrances, men prefer caramelized fragrances and the LGBTI group prefer woody ones. In addition, through the BIOPAC tool (applied to 10 students), the influential zone was established in the decision when buying perfumes. In the case of women, the findings revealed that in the frontal lobe there was a strong cerebral activation while they were exposed to different fragrances, contrary to how men reacted to them. Finally, with the EYE TRACKING, the study showed that, women go more into detail when acquiring a product than men, who just pay attention to basic characteristics of the product. Keywords: Neuromarketing, neuroscience, purchase decision, sensory stimulation. JEL Classifications: M31, M39 DOI: https://doi.org/10.32479/irmm.8963